The effects of the combination treatment of AR and FGFR inhibitors in prostate cancer - Kim, Yu (My University, 2021)
Androgen receptor (AR) signaling is key for prostate cancer (PrCa) progression. Androgen deprivation therapy is not curative if PrCa progresses to advanced, castration-resistant PrCa and androgen-independent cancers. Fibroblast growth factor receptor (FGFR) signaling is a possible bypass mechanism of AR dependency, and represents a therapeutic target against PrCa. The aim of this thesis was to compare the effects of single and combination drug treatments using respective, small-molecule inhibitors of AR and FGFR signaling in 2D and organotypic 3D cell culture. Another aim was the quantitative evaluation of the effects of drug treatments on the proliferation and viability of cells. LNCaP, CWR-R1 were treated with AR antagonists; Enzalutamide, Darolutamide, and concentration series of the 2nd generation FGFR inhibitors; FIIN-1, FIIN-2 in single and combinatorial treatment. Drug responses were evaluated by measuring proliferation, viability, and immunofluorescence staining of cells and organoids. In addition, morphological differences by the effect of drug treatment were quantified by automated image analysis. The combination treatment reduced proliferation and viability in 2D and 3D, but the reduction was greater in 3D particularly in high concentration. Moreover, Enzalutamide and FIIN-2 combinations were more effective in LNCaP and CWR-R1, respectively. However, cell death, smaller cell and organoids were observed only in high concentrations of the combination treatment. In conclusion, combination drug treatment has a moderate additive effect. The effects of the drug treatment were more pronounced in 3D than 2D due to in vivo-like conditions and Enzalutamide with FIIN-2 combination was the most effective combination against PrCa cells.
Keywords: Prostate cancer, Combination drug treatment, AR and FGFR signaling, Organotypic 3D cell culture